Learning about Job Search: A Field Experiment with Job Seekers in Germany - Steffen Altmann; Armin Falk; Simon Jäger; Florian Zimmermann (Institute for the Study of Labor (IZA), 2015)
We conduct a large-scale field experiment in the German labor market to investigate how information provision affects job seekers' employment prospects and labor market outcomes. Individuals assigned to the treatment group of our experiment received a brochure that informed them about job search strategies and the consequences of unemployment, and motivated them to actively look for new employment. We study the causal impact of the brochure by comparing labor market outcomes of treated and untreated job seekers in administrative data containing comprehensive information on individuals' employment status and earnings. While our treatment yields overall positive effects, these tend to be concentrated among job seekers who are at risk of being unemployed for an extended period of time. Specifically, the treatment effects in our overall sample are moderately positive but mostly insignificant. At the same time, we do observe pronounced and statistically significant effects for individuals who exhibit an increased risk of long-term unemployment. For this group, the brochure increases employment and earnings in the year after the intervention by roughly 4%. Given the low cost of the intervention, our findings indicate that targeted information provision can be a highly effective policy tool in the labor market.
Keywords: C93; D04; D83; J64; J68; 330; job search; information provision; unemployment; field experiment